PENGELOLAAN PONDOK PESANTREN MODERN: (Studi Kasus di Pondok Pesantren Sultan Hasanudin Makassar) - Miftahu Rahmi Suwardi; Sheila; A Zakiyah Farhanah; Arismunandar; Ahlun Ansar (Jurnal Studi Pesantren, 2025)
The management of Islamic boarding schools (pesantren) has undergone significant transformations to adapt to the demands of modern education while preserving their traditional values. This study examines the management practices of Sultan Hasanuddin Modern Islamic Boarding School in Gowa, Indonesia, which integrates Islamic teachings with contemporary education. Using a qualitative descriptive method, the research explores the institution's operations, curriculum, and human resource management through interviews, direct observation, and document analysis. Findings reveal that the pesantren employs a comprehensive student admission process, emphasizing religious understanding through academic tests, Qur'an recitation assessments, and interviews. The dual-track curriculum combines the national curriculum (K13 and Merdeka) with tahfidz programs, fostering both academic and religious excellence. Modern educational technologies, such as computers and iPads, enhance the learning experience, while state-of-the-art facilities provide a conducive environment for students The pesantren’s achievements in academic, religious, and extracurricular fields underscore the success of its holistic management approach. This study highlights the potential of pesantren as exemplary models of integrated education, balancing traditional and modern pedagogical practices.